2013
DOI: 10.1128/jcm.01573-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Subtyping of Clinically Relevant Human and Ruminant Mycoplasmas by Use of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: g Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) recently emerged as a technology for the identification of bacteria. In this study, we aimed to evaluate its applicability to human and ruminant mycoplasmal identification, which can be demanding and time-consuming when using phenotypic or molecular methods. In addition, MALDI-TOF MS was tested as a subtyping tool for certain species. A total of 29 main spectra (MSP) from 10 human and 13 ruminant mycoplasma (sub)speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 42 publications
4
66
0
Order By: Relevance
“…This has also been shown previously by Pereyre et al who successfully applied this technique for the identification of Mycoplasma spp, including M. hominis isolates. 6 In our case of M. hominis CNS infection, MALDI-TOF MS was a reliable tool and the use of 16S rDNA sequencing could have been avoided.…”
Section: Discussionmentioning
confidence: 94%
“…This has also been shown previously by Pereyre et al who successfully applied this technique for the identification of Mycoplasma spp, including M. hominis isolates. 6 In our case of M. hominis CNS infection, MALDI-TOF MS was a reliable tool and the use of 16S rDNA sequencing could have been avoided.…”
Section: Discussionmentioning
confidence: 94%
“…Protein extracts were prepared as described previously from 1 ml of 48 h broth cultures (Pereyre et al, 2013). The final pellets were dissolved in an equal volume (20 ll) of 70% formic acid and acetonitrile.…”
Section: Maldi-tof Analysismentioning
confidence: 99%
“…However DNA rearrangements were shown to occur within the vsp loci in clonal populations (Buchenau et al, 2010;Lysnyansky et al, 1996) so their use for subtyping strains with an epidemiological concordance was limited. In contrast the overall protein patterns obtained by MatrixAssisted Laser Desorption Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS) were shown to be promising for subtyping strains of M. bovis (Pereyre et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, a study using MALDI-TOF MS to identify and type Mycoplasma genus members found that 96% of Mycoplasma strains can be identified at the species level. For typing purposes, MALDI-TOF MS was shown to cluster M. bovis and M. agalactiae isolates by their year of isolation and genome profile, respectively, and M. pneumoniae isolates by their adhesion p1 type using the MALDI-TOF Biotyper software (28). Here, a novel strategy for typing type 1 and type 2 M. pneumoniae strains using the MALDI-TOF MS ClinProTools system was developed.…”
Section: Discussionmentioning
confidence: 99%